Giant simple biliary cyst infection treated with minimally invasive percutaneous drainage - Rocha, Rafael; Falsarella, Priscila; Pereira De Azevedo, Andre; Garcia, Rodrigo (World Journal of Nuclear Medicine, 2018)
We describe a minimally invasive alternative approach in a patient with infected hepatic cyst to stabilize the patient before definitive surgery. A 58-year-old man presented with fever and hypotension after 2 weeks of asthenia, chills, weight loss, slight abdominal pain, and a previous asymptomatic simple hepatic cyst. On ultrasound, a giant heterogeneous hepatic cyst with thick wall was noted. A positron emission tomography-computed tomography scan was indicated and demonstrated high uptake (standardized uptake value = 7.6) in the wall of the cyst, suggestive of infection. He underwent percutaneous drainage guided by the tomography. A 12 Fr drain was positioned inside the collection and 5 L of purulent material was aspirated from the cyst, and at day 12th, surgical resection was performed. Histopatological analysis confirmed a simple biliary cyst. The patient remains asymptomatic on 1-year follow-up. Percutaneous drainage before surgical treatment allowed the definitive approach to be performed with the patient in better clinical conditions.
Keywords: Giant biliary cyst; percutaneous drainage; pyogenic hepatic cyst